The evolutionary game and simulation of key players in the green supply chain of construction industry - Na Zhang; Ke Bin Lu (Modern Supply Chain Research and Applications, 2022)
Purpose This research studies the behavior choice of key actors in the construction supply chain and constructs a model which includes the benefit function of the government, contractors and owners, aiming at improving the coverage of green buildings. Design/methodology/approach In this paper, tripartite dynamic game is studied and simulated based on duplicate dynamic equation. The tripartite game under government intervention is rarely considered, and government punishment measures are seldom introduced into the research. Findings According to the simulation results, the practical insights in line with the development of green supply chain are put forward. Rewards and punishments affect the development of the supply chain. New technologies and new materials accelerate the development of green supply chain and then improve the coverage of green buildings. Research limitations/implications This paper constructs a dynamic model based on complete information rationality, which is difficult to realize in practice, for information is incomplete and human rationality is limited. Originality/value In fact, the government has not issued a punishment document to introduce a new variable adjustment model.
Keywords: 650; Construction industry; Evolutionary game; Green supply chain; Simulation analysis